Worker Deaths: A Regional Autopsy Study - Boz, Halil; Ketenci, Hüseyin Çetin; Demir, İbrahim and Aydoğdu, Halil İlhan and Askay, Mehmet and Özer, Erdal and Beyhun, Nazım Ercüment (The Bulletin of Legal Medicine, 2021)
According to the International Labor Organization, every 15 seconds 153 workers are injured and one worker dies because of occupational accidents or diseases. Every day, 6300 people die in the world due to occupational accidents or work-related diseases. Forensic investigation documents and autopsy reports of patients who were autopsied between 2011-2015 at the Forensic Medicine Department of Morgue Specialization in Trabzon Group Presidency and whose causes of death were related to occupational accidents were examined retrospectively. It was determined that 111 (99.1%) were male and 1 (0.9%) were female from a total of 112 worker deaths. Their ages ranged between 18 and 64. When the distribution of cases by business types was analyzed, it was determined that 61 (54.5%) cases worked in the construction sector and 12 (10.7%) in the energy sector. It was determined that work accidents occurred due to falling from height in 34 (30.4%) cases and electric shock in 19 (17%) cases. There were skull bone fractures in 44 (39.3%) cases and rib cage fractures in 22 (19.6%) cases during autopsies. In histopathological examinations; there were cardiovascular pathologies in 13 (11.6%) cases, edema and bleeding in the lungs in 20 (17.9%) cases. In accordance with the national work accident statistics, according to the results of this study; the first place is the construction sector. As a cause of death, general body traumas, electric shocks and work machine accidents due to falling from high come to the fore.